Eksistensi Ketuhanan Yang Maha Esa Dalam Regulasi Pendirian Rumah Ibadah - Manotar Leryaldo Sinaga; Yakobus Ndona (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is to determine the existence of the Almighty God in the Regulations for Establishing Houses of Worship. In this research the author uses normative legal techniques which are library research, which is carried out by examining all laws and regulations related to the problem that is the object of this research. This research is intended to find out the regulations for establishing places of worship in the Joint Regulations of the Minister of Religion and the Minister of Home Affairs Number 9 and 8 of 2006 based on the principles of the one and only God. The results of this research indicate that there is inequality in establishing places of worship for minority groups due to the requirements in these regulations being dominated by the majority group.